Effects of pharmacogenomics-guided treatment on medication adherence and the antidepressant switching rate in major depressive disorder - Chen, Chaoli; Lun, Yang; Yu, Jing; Zhao, Xiaochuan; Su, Shi; Zhao, Mengqiang; Yan, Yuhang; Wang, Jiaqi; Fu, Ran; An, Feiyue; Duan, Liguang; Yan, Leting; et al. (Frontiers in Pharmacology, 2024)
Background:In the treatment of depression, medication plays a crucial role.However, insufficient patient adherence to medication often results in unsatisfactory treatment outcomes, increasing both the recurrence and rehospitalization rates of depression, and consequently imposing a greater economic burden on the healthcare system. Objectives:Our objective was to examine the impact of pharmacogenomic testing on medication adherence and antidepressant switching rates among individuals diagnosed with depression. Methods:This retrospective cohort study encompassed patients diagnosed with depression who were admitted to the First Hospital of Hebei Medical University between April 2022 and September 2023. Patients were categorized into a pharmacogenomics-guided treatment (PGxT)group and a treatment as usual (TAU) group based on whether pharmacogenetic testing was conducted. The primary outcome measures included the proportion of patients exhibiting medication adherence greater than 80% at three and six months post-discharge, as well as the proportion of patients experiencing changes in their prescribed medication types. Results:A total of 310 patients in the PGxT group and TAU group were obtained through propensity score matching. Among the 620 patients in both groups, 57.42% demonstrated good adherence (≥ 80%) at three months; this percentage dropped to 31.45% at six months. At three months of observation, the percentages of patients demonstrating good adherence were significantly different between the groups (64.52% in the PGxT group vs. 50.32% in the TAU group; p < 0.001). The difference was also significant after six months (38.06% in the PGxT group vs. 24.84% in the TAU group; p < 0.001). Furthermore, patients receiving PGxT (20.64%) exhibited a lower rate of antidepressant conversion compared to those receiving TAU (31.29%). Conclusion:The findings of this study indicate that pharmacogenomics testing positively influences treatment adherence and may decrease the need to switch medications among patients with depression.